Expectativas da família em relação à escolarização do seu filho com altas habilidades - Oliveira, Marilú Palma de (2009)
The present dissertation developed in the Research Line Special Education brings as theme, families expectations and as general aim, as I want to investigate, verify the expectations of high abilities/giftedness students family regarding to the school role in their child s life. To reach this goal, it was outlined some specifics, such as: identify the expectations of families related to the school performance along with their child; verify along with the Educational Institution how actions are reflected on children s education and investigate the families conceptions about the school treatment/attendance to this student. Making clear that this research is characterized as qualitative, as well as descriptive, reporting it as a case study, since it involves a group for intensive analysis of a particular situation. The issue raised on this research, found in here, was: What expectations the high/giftedness students families have regarding to their education? For data collection it was used instruments like: field journal, for observation recordings and semi-structured interviews with moms that represent this social group. The information analysis was realized from registers. Considering their speeches and the observation recordings, it was chosen the data analysis throughout the chapters by juxtaposing theorists in evidence. In data analysis, contained in the mother s speeches, it was verified they value the school on its dimension of forming individual and social values. They comprehend that the school doesn t attend their children s necessities and that their context, in many situations, show attitudinal barriers almost insurmountable to their schooling process. Therefore, they found at the school a place with some limitations for attending their children educational necessities. This perspective, it s pointed as expectations formation of an adult under ethical principals and moral favorable in their professionalization process. So, the research, besides revealing hope that the families still deposit in school as educational institution, it also showed that they want and are willing to form a support net for better development and use of students potential. From then, endorse the importance of the school acceptance for changing information about their children s differences. Finally, it can be considered that the school has condition to attend such expectations if it shares fears, insecurities and frustrations before challenges posed by the diversity of its students. By doing so, they have family as a partner and not rival or competitor.